Residues of helix ɑ2 are critical for catalytic efficiency of mycobacterial alkylhydroperoxide reductase subunit C - Chong, Shi Min Sherilyn (2021)
The ability of Mycobacteria to overcome oxidative stress is of paramount importance for its survival within the host. One of the key enzymes that are involved in protecting the bacterium from reactive oxygen species is the catalase-peroxidase (KatG). However, in strains resistant to the antibiotic isoniazid, KatG is rendered ineffective, which is associated with an increased expression of alkylhydroperoxide reductase subunit C (AhpC). Mycobacterial AhpC possesses a unique helical displacement when compared to its bacterial counterparts. Here, via mutagenesis studies, we demonstrate the importance of this helix for redox modulation of the catalytic activity of AhpC. Along with structural insights from crystallographic data, the impact of critical residues on the structure and flexibility of the helix and on AhpC oligomerization is described.